The handbook of global agricultural markets : the business and finance of land, water, and soft commodities - Nijs, Luc.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book is a one-stop reference for practitioners and academics in finance, business and economics, providing a holistic reference to the international agriculture business. It takes a multidisciplinary approach, looking at the issues, opportunities and investable themes in the global agricultural space, combining research and practical tools.
Keywords: Science